Teachers’ professional identity construction on Facebook using the teacher-student interaction perspective - Santoso, Nobertus Ribut; Nombrado, Marlon; Yumul, Shelly de Vera; Mariano, Raymond M.; de Guzman, Ma. Theresa (Jurnal Studi Komunikasi, 2021)
Teachers’ professional identity is created in the dynamic process of interpersonal interaction. This research aims to investigate how teachers negotiate their interpersonal role identities across physical and digital student-teacher interactions. By employing a descriptive qualitative design, this research used the ethnographic method. An interview guide was designed to seek an in-depth understanding of this phenomenon by gaining insights from ten high school teachers from Metro Manila. After collecting the data, an inductive approach is used to analyse the data. The research reveals that the teachers’ interpersonal identity standards and their appraisal of their interaction with their students on Facebook and their network logic align and are congruent with one another. The teachers’ interaction with their students online and offline is always guided by their perceived roles and responsibilities and their limitations and boundaries as teachers.